Investigating the air quality index inside two museums in Baghdad City - Ezz Aldeen, Shaymaa A.; Fleeh, Nada Abdul Rahman (Iraqi Journal of Science, 2025)
The study aims to investigate and assess the indoor air quality within two renowned museums situated in Baghdad city, namely the Iraqi National Museum and the Natural History Museum, during the months of October and November 2023. A Temtop device was used to measure the main indoor environmental parameters in these museums, particularly (total volatile organic compounds (TVOC), formaldehyde (HCHO), particulate matter (PM), temperature, and humidity), as well as Air Quality Index (AQI). The average concentrations of different air pollutants measured in both museums were as follows: TVOC was 0.93 mg/m3 and 0.80 mg/m3, HCHO was 0.31 mg/m3 and 0.28 mg/m3, PM2.5 was 57.23 μg/m3 and 52.33 μg/m3, and PM10 was 85.11 μg/m3 and 72.82 μg/m3. The average values of TVOC were within the limits recommended by the World Health Organization (WHO) and Environmental Protection Agency (EPA), which is less than 1mg/m³. Meanwhile, the average values of the rest of the indoor pollutant concentrations exceeded the recommended limits, which for HCHO is 0.004 mg/m3 and for, PM2.5 is 35μg/m3, and PM10 is 150µg/m3, for the daily standard. The average values of indoor air temperature for the two museums were higher than the ASHRAE standards recommended limits. In contrast, Indoor RH is below the recommended limits. As for AQI, it was classified as unhealthy for sensitive groups for both museums.